A Memorial Day for the Books Annihilated in the Holocaust: History and Reason - Hershkowitz, Isaac (The review of rabbinic Judaism, 2024)
This article focuses on a Memorial Day ceremony that was regularly held during the State of Israel’s first two decades to honor the holy books destroyed during the Holocaust. The ceremony aimed to commemorate the Nazis’ attempt to destroy Judaism, not just the Jewish people. At the forefront of these efforts was Shmuel Zanwil Kahana, who sought to create a mystical atmosphere during the ceremony. His goal was to approach the new altar, represented by the furnace at Mount Zion, and offer a sacrifice of exilic literature to arouse a new spirit within the people of Israel. Despite his almost occult practices and liturgy, Kahana did not achieve the results for which he hoped. His attempts to build the nation through the destruction of its exilic spirit did not succeed.